Chapter Introduzione - Territorialismo, eco-territorialismo, bioregionalismo. Genesi, contesti, motivazioni - Marzocca, Ottavio (Territori, 2023)
The essay traces back the maturation of eco-territorialism starting from the late 1970s 'rediscovery' of the territory, coinciding with the crisis of the Fordist model, the rise of the diffuse factory and the beginning of globalisation processes. In the evolutions and involutions of such scenario up to the recent pandemic and the Russian-Ukrainian war, the advocates of eco-territorialism find reasons to challenge the unlimited urbanisation of space; to frame the question of dwelling as an unavoidable ethical-political problem; to overcome the reductionism of those who read the ecological crisis as a mere climate change or energy issue; to problematise and radically redefine the ideas of development and planning, reconnecting them to the self-sustainable reconstruction of material and immaterial relations between the inhabitants and the anthropic, ecosystem and bioregional complexity of places.